Patience, Paratext, and the Heteronomy of Critique: An Introduction to Reading Politics of Piety at 20 Years. - Iqbal, Basit Kareem (Religious Studies Review (John Wiley & Sons, Inc.), 2025)
The article discusses the significance of Saba Mahmood's work, "Politics of Piety," particularly in relation to the themes of patience, agency, and the interplay between politics and analysis. It highlights Mahmood's ethnographic exploration of the concept of sabr (patience) among women in Egyptian society, emphasizing that patience can be a form of active engagement rather than mere acceptance of injustice. The text also critiques the limitations of secular critique and the need for a nuanced understanding of different forms of subjectivity and ethical self-formation, arguing that analysis should not be conflated with political action. Overall, the article underscores the importance of interpretive activities in understanding complex social dynamics and the relationship between individuals and their socio-political contexts.